COMPARATIVE-LEGAL ANALYSIS OF TYPOLOGICAL FEATURES OF INSTITUTIONS OF REPRESENTATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article presents the variety of typologies of institutions of representation. They are especially important during the period of democratization of the political system of Kyrgyzstan as a sovereign state. The purpose of this article is to analyze existing typologies that develop and specify existing ones, and at the same time supplement empirics with new knowledge through the prism of the theory of constitutional law. Touching upon this key problem for our research, we would like to dwell on the typology, taking into account those concepts that are formulated in science, taking into acccount post-Soviet countries, including Kyrgyzstan. In the process of analysis, a typology is proposed based on system- forming characteristics - democracy, absolutism, the relationship between various branches and institutions of power - presidential republic, parliamentary republic, etc., forms of state territorial-administrative structure (unitary state, federation and confederation). In the article, the analysis methodology was built on the well- known principles of dialectics, taking into account specific private scientific methods of analogy, comparison, structural method, analysis and synthesis. The conclusions presented in the article are of practical importance for their use in the work of government bodies in Kyrgyzstan in the development of national programs and concepts.
Keywords: democracy; state; typology; constitution; representative bodies of power; the role of elections; constitutional law.